Between New Education and Idealistic vision: Giuseppe Lombardo Radice and the Arduous Path of L’Educazione Nazionale in Italy (1927-1933). - Todaro, Letterio (Swiss Journal of Educational Research, 2019)
Opening the issue of Pour l’ère nouvelle (January 1927), Adolphe Ferrière announced that L’Educazione Nazionale, directed by Giuseppe Lombardo Radice, would be the Italian partnership of the educational press officially committed with the New Education Fellowship. The strong relation between the two scholars was based on a shared vision of education as really focused on the release of children’s natural energies. The cultural mission of the Italian journal was not an easy one to accomplish, due to the increasingly heavy atmosphere characterizing the Italian public life, signed by the turning of Fascism into an authoritarian Regime. Up to the turning point of the thirties the review often tried to draw attention onto several themes and figures related to the progressive expansion of the New Education. Unfortunately, the involution of Fascism hindered the journal’s activity, finally forcing its closure in 1933.